2021
DOI: 10.3390/nu13020633
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cooking Patterns with Inflammatory and Cardio-Metabolic Risk Biomarkers

Abstract: Diet has been clearly associated with cardiovascular disease, but few studies focus on the influence of cooking and food preservation methods on health. The aim of this study was to describe cooking and food preservation patterns, as well as to examine their association with inflammatory and cardio-metabolic biomarkers in the Spanish adult population. A cross-sectional study of 10,010 individuals, representative of the Spanish population, aged 18 years or over was performed using data from the ENRICA study. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Our ndings are consistent with a previous study which reported that high consumption of deep-fried foods and low intake of steamed, boiled, and raw food were signi cantly associated with hyperlipidemia [8]. Another related study also showed that boiling and sautéing, brining, and light frying tend to be cardio-metabolically bene cial [13]. The possible mechanism for this is that steaming increases the concentration of polyphenols and antioxidants [18], and dietary polyphenols have the effect of lowering LDL-C [19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our ndings are consistent with a previous study which reported that high consumption of deep-fried foods and low intake of steamed, boiled, and raw food were signi cantly associated with hyperlipidemia [8]. Another related study also showed that boiling and sautéing, brining, and light frying tend to be cardio-metabolically bene cial [13]. The possible mechanism for this is that steaming increases the concentration of polyphenols and antioxidants [18], and dietary polyphenols have the effect of lowering LDL-C [19].…”
Section: Discussionsupporting
confidence: 92%
“…For example, frying food causes water to be replaced by fat, and deep frying results in an increase in trans-fatty acids [11]. Studies have found that frequent consumption of fried foods is associated with a higher risk of hypertension [12], and the social business cooking patterns have shown a relationship with in ammatory and cardio-metabolic health biomarkers [13]. However, the relationship between cooking patterns and hyperlipidemia is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the study of cooking methods could provide interesting insights into the investigation of chronic diseases development given that many of these are related to changes in inflammatory, renal, and other nutritional biomarkers 11 , 12 . Thus, in a previous large-sized study, cooking patterns showed a relationship with inflammatory and cardio-metabolic health biomarkers 13 . More specifically, four cooking patterns were found: (a) The “Spanish traditional pattern”, characterized by boiling, sautéing, brining, and pan-frying, tended to be metabolically advantageous; (b) the “Health-conscious pattern”, based on battering, frying, and stewing, seemed to improve renal function; (c) the “Youth-style pattern”, with frequent consumption of soft drinks and distilled alcoholic drinks, and low consumption of raw food, was associated with metabolic benefits, except for a higher insulin and higher urinary albumin levels; and (d) the “Social business pattern”, rich in fermented alcoholic drinks, food cured with salt or smoked, and cured cheese, appeared to be detrimental for lipid profile, renal function and other metabolic biomarkers.…”
Section: Introductionmentioning
confidence: 74%
“…It has been found that chemicals produced by cooking meat at high temperatures (grilling/barbecuing) can induce inflammation, oxidative stress, and insulin resistance, and consequently lead to damage of the inner vascular wall and development of atherosclerosis. All of these processes increase the risk of developing high blood pressure and the likelihood of MetS [19]. In contrast, Heller et al [20] examined the effect of daily consumption of 8 oz.…”
Section: Discussionmentioning
confidence: 99%